Central sleep apnea during continuous positive airway pressure therapy in obstructive sleep apnea patients: from the compliance to adaptation, maladaptation and reflexes - Lombardi, Carolina; Caravita, Sergio; Parati, Gianfranco (Journal of Thoracic Disease; Vol 9, No 11 (November 29, 2017): Journal of Thoracic Disease (Quantitative Imaging of Thoracic Diseases), 2017)
Obstructive sleep apnea syndrome (OSAS) is the most common form of sleep-disordered breathing. Untreated OSAS is associated with an increase in comorbidities, mortality risk, health care costs, and traffic accidents (1). However, OSAS is susceptible to treatment by various approaches, the gold standard being the application of continuous positive airway pressure (CPAP), especially when OSA is severe and when it is associated with excessive daytime sleepiness (2).